Deconstruction and psychology understanding the context of power, ambiguity, and impermanence of knowledge and its pedagogical implications. [article]. - Tiangco, Joseph Anthony Narciso Z.
Critical emancipatory reflection leads to a suspicion of the use of Metanarratives in mainstream psychological discourse. Metanarratives have bred marginalization in the context of power struggles by the status quo to maintain their priviledged position within society and the scientific community of psychology. Thus, accounts of politicized ideological enmity characterized the economics of psychological research dissemination. Following Lyotard's notion of incredulity towards metanarratives, the paper explicates the necessitated decostructibility of knowledge in the psychological sciences. By doing so, the author presents the limits of knowledge in psychological discourse given the language games that permeate both quantitative and qualitative research methods. In effect, hermeneutical difficulties render the epistemic foundations of psychology towards ambiguity and impermanence, Correlatively, though the postmodern condition may have been characterized as a nihilistic demise, the author argues that the use of dogma concurs the assimilation of polaristic extremes such as pluralism and dogmalism amongst psychological texts. Understanding the context of power, ambiguity, and impermanence of knowledge rightfully situates the interrelationship between the deconstruction and psychology. Quintessentially therefore,pedagogical implications in the transmittance of knowledge in psychology should not left unturned. Imparting knowledge in psychological sciences should be re-evaluated vis-a-vis the postmodern condition. The author proposes that the end goal of present pedagogies should work towards achieving a psychology wherein scholars sojourn in joyful confusion. And perhaps someday, they may contribute to the emergence of a new generation of psychologist that espouse open-mindedness and tolerance for varying ideologies.